Contra la guerra y el peronismo. Las imágenes de Ricardo Warecki en el diario Crónica de Rosario - Veliscek, Elisabet (CALLE14: revista de investigación en el campo del arte, 2021)
The article analyzes the political cartoons, advertisements and illustrations of artist Ricardo Warecki published by the newspaper Crónica de Rosario (Argentina) between 1945 and 1947, in the context of the national and international events that drove economic and political changes during the second postwar period, the beginning of the cold war and the rise of Peronism. The social transformations that were taking place around the world were registered by the satirical gaze of the artist, and graphic humor was used as a way to show his dissatisfaction with the advance of violence and authoritarianism.